Cloud computing based smartphone social authentication system - Yan-bing LIU; Fei-fei LIU (Tongxin xuebao)
Cloud computation provided the capabilities to store and compute infinitely,which can filled the gap of resource constrain.So a cloud-computation based social authentication system for smartphones aimed at the problem that the present authentication methods require a long period of validity of the authentication tokens and make the terminals consume large resources was proposed.The system took three types of social networking features into considered,which were different certification authority between the friends,behavior differences between individual and trust level carried by each interactive event.The results of experiments show that the system can effectively solve the problem that system performance will sharply decline when the expiry date of authentication tokens is short.